JFK : public, private, secret - Taraborrelli, J. Randy (St. Martin's Press, 2025)
"From the New York Times bestselling Kennedy historian and author of Jackie: Public, Private, Secret comes the other side of the story -- her husband's: JFK: Public, Private, Secret. In this deeply researched presidential biography, J. Randy Taraborrelli tells John F. Kennedy's story in a provocative new way by revealing how public moments in his life were so influenced by private relationships with not only his family, but also Jackie's. But it's the secret life that also surprises. As Congressman, Senator and finally President, JFK was a magnet for women. With exclusive interviews and meticulous research, Taraborrelli reveals not only the man's many affairs but also the strength and resolve his wife showed in coping with them. JFK's women include: Jackie Kennedy, and her rules of engagement for Jack's infidelity: "Show me some respect and don't rub it in my face". Inga Arvad. JFK's first love and how it ended over fears she was a Nazi spy. Marilyn Monroe. Why Jackie insisted JFK end it with her: "This one's different, Jack. This one's trouble!" Finally -- the truth about of JFK's relationship with Marilyn exclusively from Marilyn's closest friend... and how it wasn't what people believed. Joan Hitchcock. The mysterious brunette who comforted Jack after Jackie threatened to file for divorce. Other great stories: How JFK's grief over his infant son caused him to make rash decisions that pulled the USA into Vietnam for the first time. The real truth, once and for all, about the Mafia's involvement in JFK's election. The startling drug abuse that clouded the President's decisions during the disastrous Bay of Pigs... and how Jackie managed to wean him from those drugs in time for the nearly cataclysmic Cuban Missile Crisis. The Kennedys' secret plans to renew their wedding vows, made just before JFK's assassination. The JFK presented in Taraborrelli's definitive biography is a complex and endlessly fascinating historical figure, despite-and maybe even because of-his many flaws". --